2016
DOI: 10.1038/ncomms12748
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ROS and upregulation of inflammatory cytokines by FoxO3a promotes survival against Salmonella typhimurium

Abstract: Virulent intracellular pathogens, such as the Salmonella species, engage numerous virulence factors to subvert host defence mechanisms to induce a chronic infection that leads to typhoid or exacerbation of other chronic inflammatory conditions. Here we show the role of the forkhead transcription factor FoxO3a during infection of mice with Salmonella typhimurium (ST). Although FoxO3a signalling does not affect the development of CD8+ T cell responses to ST, FoxO3a has an important protective role, particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 70 publications
2
31
0
1
Order By: Relevance
“…In concordance with this, we observed that knockingdown of FOXO3 expression, using specific siRNA, resulted in a significant increase of BCG-induced transcription and secretion of IL-10. This data is in agreement with a previous study that reported a higher expression of IL-10 by neutrophils, monocytes and macrophages from FOXO3 −/− mice infected with Salmonella typhimurium, as compared to non-infected mice (44). Moreover, it was shown that T cells from FOXO3 −/− mice express higher levels of IL-10 compared to wild type ones (45).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In concordance with this, we observed that knockingdown of FOXO3 expression, using specific siRNA, resulted in a significant increase of BCG-induced transcription and secretion of IL-10. This data is in agreement with a previous study that reported a higher expression of IL-10 by neutrophils, monocytes and macrophages from FOXO3 −/− mice infected with Salmonella typhimurium, as compared to non-infected mice (44). Moreover, it was shown that T cells from FOXO3 −/− mice express higher levels of IL-10 compared to wild type ones (45).…”
Section: Discussionsupporting
confidence: 93%
“…Our data correlate with the previous reported protective role of FOXO3 against Salmonella typhimurium (ST) infection. Indeed, FOXO3 signaling inhibited IL-10 secretion with a concomitant induction of inflammatory immune responses in mice infected with ST, leading to the control of the intracellular bacteria (44). Several studies pointed that M.tb successfully engages activators of IL-10 transcription such as STAT3 and ReIB during infection to abolish the protective response mounted by the host and ensures its survival and persistence (11,52).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to H. vulgaris, FoxO modulates the innate immune system in mouse, [25] Drosophila, [26] and C. elegans. [28] Functional analyses in C. elegans and Drosophila have verified that the level of FoxO expression is indeed directly linked to life span without detectable costs for the individuals. [25] FoxO signaling has been shown to reduce susceptibility to bacterial infections by reducing oxidative stress and induction of inflammatory cytokines.…”
Section: Microbiome Composition and Interorgan Crosstalk In The Elderlymentioning
confidence: 98%
“…Several reports suggest that FOXO3a may mediate macrophage apoptosis under stress conditions . On the contrary, FOXO3a can also sustain the pro‐inflammatory state of macrophages by regulating the extracellular signal‐regulated kinase signalling pathway to curb reactive oxygen species production without altering cell death during host defence response . Nie et al .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] On the contrary, FOXO3a can also sustain the pro-inflammatory state of macrophages by regulating the extracellular signal-regulated kinase signalling pathway to curb reactive oxygen species production without altering cell death during host defence response. 17 Nie et al have demonstrated that FOXO3a represses interleukin-13 transcription in macrophages to protect against bleomycin-induced pulmonary inflammation and fibrosis. 18 In addition, it has been shown that FOXO3a is capable of inhibiting the NLRP3 inflammasome by potentiating the transcription of Bim in liver macrophages (Kupffer cells).…”
Section: Introductionmentioning
confidence: 99%